Demystification of fermented foods by omics technologies. (August 2022) - Chen, Wanping
Abstract : Microbial fermentation leading to the production of foods and beverages is an ancient bioprocess but still practices worldwide to date. Despite the great economic, cultural, and social values of fermented foods, only a small part of them is well understood; however, most of them are still in a mysterious state to a certain extent. In recent years, the emerging omics techniques have been actively applied to explore the mysteries of fermenting processes for fermented foods worldwide, which could provide a comprehensive perspective to track fermentation systems. This review summarized the application of different types of omics techniques in fermented-food research based on the recent representative studies and predicted that microbiomics and foodomics would be the two main trends in the research of fermented foods.